(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
The assumption that undertakings in digital markets will, as in “traditional” ones, compete among each other to provide always better and diverse products and services, and that users will be allowed to easily find these products and services, compare them and choose those that suit them best, turned out to be incorrect. The same happened with the assumption that existing EU and national competition law will be able to effectively address issues that occur in digital markets and that are (usually) a consequence of the anti-competitive behavior of the biggest digital undertakings. The purpose of the paper is to examine why and how these digital undertakings cope to escape control of the competition authorities, and what are new solutions that are proposed at the EU and national level to strengthen competitiveness in digital markets. Therefore, we will firstly single out few main characteristics of digital markets, then identify challenges that competition law faces in these markets due to the presented characteristics. In the fourth and the main part of the paper, we will present key provisions proposed in the draft Digital Markets Act to complement competition law and ensure contestable and fair digital markets across the EU. We will thereafter present some of the new national competition rules recently adopted in Germany, which are similar to those proposed under the draft Digital Markets Act.